Fluorescence-Guided Surgery - Nagaya, Tadanobu; Nakamura, Yu A.; Choyke, Peter L.; Kobayashi, Hisataka (Frontiers in Oncology, 2017)
Surgical resection of cancer remains an important treatment modality. Despite advances in preoperative imaging, surgery itself is primarily guided by the surgeon’s ability to locate pathology with conventional white light imaging. Fluorescence guided surgery (FGS) can augment what the surgeon sees by accentuating sites of disease and defining tumor margins during the procedure. Intraoperative visualization of tumors may not only allow more complete resections but also improve safety by avoiding unnecessary damage to normal tissue which can also reduce operative time and decrease the need for second-look surgeries. A number of new FGS imaging probes have recently been developed, complementing a small but useful number of existing probes. In this review, we describe current and new fluorescent probes that may assist FGS.